2023
DOI: 10.1007/s00146-023-01654-9
|View full text |Cite
|
Sign up to set email alerts
|

Using AI to detect panic buying and improve products distribution amid pandemic

Abstract: The COVID-19 pandemic has triggered panic-buying behavior around the globe. As a result, many essential supplies were consistently out-of-stock at common point-of-sale locations. Even though most retailers were aware of this problem, they were caught off guard and are still lacking the technical capabilities to address this issue. The primary objective of this paper is to develop a framework that can systematically alleviate this issue by leveraging AI models and techniques. We exploit both internal and extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…The quantitative models were seldom verified except in Govindan et al [ 70 ] and Shoukat et al [ 71 ], who used statistical analysis to evaluate the demand. It has been demonstrated that data-driven frameworks and AI can detect demand anomalies raised by panic [ 74 , 75 ]; however, these models do not predict future demand by influencing factors or propose intervention plans.…”
Section: Research Review On Panic Buying Behaviormentioning
confidence: 99%
“…The quantitative models were seldom verified except in Govindan et al [ 70 ] and Shoukat et al [ 71 ], who used statistical analysis to evaluate the demand. It has been demonstrated that data-driven frameworks and AI can detect demand anomalies raised by panic [ 74 , 75 ]; however, these models do not predict future demand by influencing factors or propose intervention plans.…”
Section: Research Review On Panic Buying Behaviormentioning
confidence: 99%